The early response gene NGFI-C encodes a zinc finger transcriptional activator and is a member of the GCGGGGGCG (GSG) element-binding protein family. - Crosby, S D (1991)
We have cloned NGFI-C, a nerve growth factor-induced early-response gene which encodes a Cys2/His2 zinc finger protein. RNA blot analysis demonstrates that NGFI-C mRNA is induced within minutes of stimulation of PC12 cells by nerve growth factor and is similarly activated in brain after a Metrazol-induced seizure. The cDNA sequence predicts a protein that contains three zinc fingers which show striking homology to the DNA-binding regions of three previously reported zinc finger proteins, NGFI-A, Krox-20, and the Wilms' tumor gene product. NGFI-C binds to the previously described DNA-binding site of these three proteins, which is GCGGGGGCG. Cotransfection experiments revealed that NGFI-C strongly activates transcription from this site in mammalian cells. The isolation of another early-response gene that encodes a member of the G(C/G)G or GSG element-binding family should provide an opportunity to investigate the relative contributions of a family of transcription factors to the cell's response to changes in its environment.